Tag, you’re it!: viral diseases in native otters of south-central Chile due to coexistence with invasive American mink and domestic dogs - Santibañez, Alexis; Coccia, Cristina; Barría, Erwin M.; Huenchuguala, Sandro; Barros, Macarena; Calvo-Mac, Carlos; Medina-Vogel, Gonzalo (Frontiers in Veterinary Science, 2025)
IntroductionBiological invasions represent a significant epidemiological route for the introduction and dispersion of pathogens, facilitating disease emergence and transmission among native biodiversity. In the temperate rainforest ecoregion of south-central Chile, the native semiaquatic mustelid Lontra felina (marine otter) and L. provocax (southern river otter) coexist both sympatrically and syntopically with two invasive species—American mink (Neogale vison) and domestic dog (Canis lupus familiaris), that act as carriers and hosts of canine parvovirus and distemper.MethodologyTo assess the occurrence of both diseases, we: (1) collected serum and mucous membrane samples from four species across three sectors of this ecoregion; and (2) employed serological immunoassays (IgG) and genetic analyses (qPCR-HRM) to detect both active and past infections, and to genotypically characterize the two viral agents.Results75% of L. felina individuals tested positive for parvovirus. The melting temperature (Tm) of the analyzed DNA fragment revealed two diverging groups, suggesting the presence of two genotypic variants of the virus within this mammalian assemblage. L. felina individuals carried the variant with the higher Tm, which was also detected in N. vison from the same locality. In contrast, L. provocax individuals carried the variant with the lower Tm, while dogs and minks hosted both viral variants. Canine distemper virus was detected only in dogs that also tested positive for parvovirus.DiscussionOur results present the first report of parvovirus in L. felina and support the hypothesis that N. vison and dogs acts as metareservoir and mink also as a bridge host for its transmission. In the study area, the synanthropic behavior of N. vison and its interactions with domestic and native species may facilitate the diversification of emergent pathogens within Chilean native fauna.